Biological differences between intrinsic and extrinsic adenomyosis with coexisting deep infiltrating endometriosis. Issue 2 (August 2019) - Khan, Khaleque N.; Fujishita, Akira; Koshiba, Akemi; Kuroboshi, Haruo; Mori, Taisuke; Ogi, Hiroshi; Itoh, Kyoko; Nakashima, Masahiro; Kitawaki, Jo
Abstract: Research question: Is there a biological difference between intrinsic and extrinsic adenomyosis with coexisting deep infiltrating endometriosis (DIE)? Design: In this prospective controlled study, biopsy specimens were collected after surgery from 23 women with intrinsic adenomyosis and 10 women with extrinsic adenomyosis with coexisting DIE lesions. Histological evaluation was carried out by immunoreaction to Ber-EP4 (epithelial cell marker) and CD10 (stromal cell marker). Tissue expression of oestrogen and progesterone receptors was analysed by immunohistochemistry. Tissue fibrosis was examined by Masson's trichrome staining with computer-based image analysis of fibrosis in respective samples. Results: The detection rate of coexistent DIE was significantly higher in women with extrinsic adenomyosis (9/10 [90.0%]) than in women with intrinsic adenomyosis (3/23 [13.0%]; P < 0.001). The pattern of Ber-EP4-stained glands and CD10-stained stromal cells of extrinsic adenomyosis was similar to that of coexistent DIE lesions. In contrast, the pattern of gland and stromal cells was similar to the endometrium in the cases with intrinsic adenomyosis. Unlike extrinsic adenomyosis, progesterone receptor expression was significantly decreased in both gland cells ( P < 0.05) and stromal cells ( P < 0.05) of intrinsic adenomyosis. Although relatively more fibrosis was seen in biopsy samples of extrinsic adenomyosis and coexistent DIE than in intrinsic adenomyosis and their coexistent DIE, no significant difference was found. Conclusions: Extrinsic adenomyosis may be considered as adenomyosis externa based on a close histological and biological relationship between extrinsic adenomyosis and coexistent DIE. Our findings may contribute to the understanding of a possible biological origin of two newly classified intrinsic and extrinsic adenomyosis.